Aggressive Antisemitism in Today's Public Discourse (KULT_online, 2011)
Antisemitism is not simply an historical phenomenon or extreme standpoint. Far from being a fringe occurrence, it is a specific system of prejudices whose stereotype pervades the middle class. The ordeal of Auschwitz and subsequent engagement with its meanings has not immunized educated society against this type of wholesale villification. In today's society, the tolerance of antisemitic expression has, in fact, greatly increased. Certain forms of expression that, up until now, occurred almost exclusively in extreme right-wing contexts and were subject to sanctions have, in the meantime, reappeared in almost all ranks of society in public language, and are said to fall under freedom-of-speech acts. This volume gathers eleven essays by experts from a range of disciplines, who turn their analytical attention here to the phenomenon of antisemitism in the middle class.